Perkembangan Inovasi Fintech di Indonesia - Yovie Bramantyo Adji; Wildan Abineri Muhammad; Abdurrachman Nurwira Lucky Akrabi; Noerlina Noerlina (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2023)
Fintech is a company that combines financial services and technology, the more technology develops, the more innovations or ideas there are about how to find solutions for financial services. This paper explains how the development of fintech innovations that already exist in Indonesia and also what are the advantages of fintech in Indonesia. Fintech in Indonesia has been running since 2006. Fintech in Indonesia is growing during the COVID-19 pandemic because Indonesians transact online. This makes fintech continue to grow in Indonesia with almost 800 fintech that already exists in Indonesia.